High-surface-capacity flexible supercapacitor and preparation method thereof
By adopting an interdigital electrode structure and a trench-shaped graphene-based electrode, combined with electrolytes such as polyvinyl alcohol, the problem that existing flexible microcapacitors are difficult to take into account between high surface capacity and mechanical properties, and the preparation of high surface capacity flexible supercapacitors is realized, with excellent mechanical properties and simple preparation technology.
Patent Information
- Application Number
- CN202311154253.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
The existing flexible microcapacitors are difficult to take into account both high surface capacity and mechanical properties, resulting in the lack of good mechanical properties in practical applications.
Using an interfinger electrode structure, trench-shaped graphene-based electrodes are prepared through 3D printing and laser etching technology, and electrolyte is mixed with polyvinyl alcohol and other materials to prepare a high-surface capacity flexible supercapacitor.
It achieves excellent mechanical properties while having high surface capacity, and is simple in preparation process and stable in structure.
Smart Images

Figure CN119581235A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of supercapacitor preparation, and in particular, relates to a high-area-capacitance flexible supercapacitor and a preparation method thereof. Background Art
[0002] The development of miniaturized smart devices has stimulated the development of micro-power sources. Due to the advantages of microcapacitors such as high power density, fast response, and long cycle life, they show great prospects in application scenarios such as personal medical care and artificial intelligence. However, due to the small size of flexible microcapacitors, small active material loading, and small capacity, their practical applications are seriously affected, and devices with high loads are subject to greater stress and thus do not have good mechanical properties. Therefore, studying the electrode structure of graphene-based microcapacitors is the key to developing flexible graphene-based microcapacitors with high surface capacity. At present, the design and preparation of a variety of electrode structures have been reported in the literature, but it is difficult to have both high surface capacity and flexibility at the same time. Summary of the invention
[0003] In order to solve the above technical problems, the present application provides a high surface capacity flexible supercapacitor and a preparation method thereof. The supercapacitor has high surface capacity and excellent mechanical properties (flexibility), and the preparation process is simple.
[0004] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:
[0005] In one aspect, the present application provides a high surface capacity flexible supercapacitor, the high surface capacity flexible supercapacitor comprising interdigital electrodes and an electrolyte;
[0006] The longitudinal section of the interdigitated electrodes is in the shape of periodically arranged grooves;
[0007] The electrolyte covers the interdigitated electrodes;
[0008] The interdigital electrodes are flexible.
[0009] Optionally, in the longitudinal section of the interdigitated electrode, the width of each groove is 50 to 200 μm;
[0010] The depth of each groove is 10 to 1000 μm;
[0011] The distance between two adjacent grooves is 10 to 80 μm.
[0012] Optionally, the thickness of the interdigital electrode is 20-2000 μm.
[0013] Optionally, the thickness of the interdigitated electrodes is independently selected from any value among 20 μm, 50 μm, 100 μm, 260 μm, 420 μm, 580 μm, 740 μm, 900 μm, 1000 μm, 1200 μm, 1400 μm, 1600 μm, 1800 μm, 2000 μm or any range therebetween.
[0014] Optionally, the mass ratio of the interdigital electrode to the electrolyte is 1:0.5-1000.
[0015] Preferably, the mass ratio of the interdigital electrodes to the electrolyte is 1:50-800.
[0016] Optionally, the mass ratio of the interdigitated electrode to the electrolyte is independently selected from any value of 1:0.5, 1:2, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:800, 1:1000 or any range between two of them.
[0017] Optionally, the raw materials for preparing the interdigital electrodes include graphene, activated carbon and additives.
[0018] Optionally, the mass ratio of the graphene, activated carbon and additive is 2 to 45:1 to 10:1;
[0019] Among them, the mass of graphene is measured by the mass of the substance itself, the mass of activated carbon is measured by the mass of the substance itself, and the mass of additives is measured by the mass of the substance itself.
[0020] Preferably, the mass ratio of the graphene, activated carbon and additive is 10-20:2-5:1;
[0021] Among them, the mass of graphene is measured by the mass of the substance itself, the mass of activated carbon is measured by the mass of the substance itself, and the mass of additives is measured by the mass of the substance itself.
[0022] Optionally, the additives include hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
[0023] Optionally, the mass ratio of the hydroxyethyl cellulose to the hydroxypropyl methyl cellulose is 1:0.5-1.5.
[0024] Preferably, the mass ratio of hydroxyethyl cellulose to hydroxypropyl methyl cellulose is 1:0.8-1.2.
[0025] Optionally, the raw material for preparing the interdigital electrode further includes water.
[0026] Optionally, the electrolyte comprises polyvinyl alcohol and sulfuric acid.
[0027] Optionally, the mass ratio of the polyvinyl alcohol to sulfuric acid is 1:0.5-5;
[0028] The mass of polyvinyl alcohol is calculated based on the mass of the substance itself, and the mass of sulfuric acid is calculated based on the mass of the substance itself.
[0029] Preferably, the mass ratio of polyvinyl alcohol to sulfuric acid is 1:0.5-1.5;
[0030] The mass of polyvinyl alcohol is calculated based on the mass of the substance itself, and the mass of sulfuric acid is calculated based on the mass of the substance itself.
[0031] Optionally, the electrolyte also includes water.
[0032] In a second aspect, the present application provides a method for preparing the above-mentioned high surface capacity flexible supercapacitor, comprising the following steps:
[0033] (1) Printing and etching a mixture containing graphene, activated carbon, additives and water in sequence to obtain interdigitated electrodes;
[0034] (2) mixing polyvinyl alcohol with water and sulfuric acid to obtain an electrolyte;
[0035] (3) The electrolyte obtained in step (2) is coated on the interdigital electrode obtained in step (1) to obtain a high surface capacity flexible supercapacitor.
[0036] Optionally, the mass ratio of graphene, activated carbon, additive and water in step (1) is 2-45:1-10:1:0.001-1000;
[0037] Among them, the mass of graphene is calculated based on the mass of the substance itself, the mass of activated carbon is calculated based on the mass of the substance itself, the mass of additives is calculated based on the mass of the substance itself, and the mass of water is calculated based on the mass of the substance itself.
[0038] Preferably, the mass ratio of graphene, activated carbon, additive and water in step (1) is 10-20:2-5:1:0.001-50;
[0039] Among them, the mass of graphene is calculated based on the mass of the substance itself, the mass of activated carbon is calculated based on the mass of the substance itself, the mass of additives is calculated based on the mass of the substance itself, and the mass of water is calculated based on the mass of the substance itself.
[0040] Optionally, the additives in step (1) include hydroxyethyl cellulose and hydroxypropyl methyl cellulose;
[0041] The mass ratio of the hydroxyethyl cellulose to the hydroxypropyl methyl cellulose is 1:0.5-1.5.
[0042] Preferably, the mass ratio of hydroxyethyl cellulose to hydroxypropyl methyl cellulose is 1:0.8-1.2.
[0043] Optionally, the thickness of the interdigital electrode in step (1) is 20 to 2000 μm.
[0044] Optionally, the thickness of the interdigitated electrodes in step (1) is independently selected from any value among 20 μm, 50 μm, 100 μm, 260 μm, 420 μm, 580 μm, 740 μm, 900 μm, 1000 μm, 1200 μm, 1400 μm, 1600 μm, 1800 μm, 2000 μm or any range between two values.
[0045] Optionally, the longitudinal section of the interdigitated electrode in step (1) is in the shape of periodically arranged grooves.
[0046] Optionally, the interdigitated electrodes in step (1) are flexible.
[0047] Optionally, in the longitudinal section of the interdigitated electrode in step (1), the width of each groove is 50 to 200 μm;
[0048] The depth of each groove is 10 to 1000 μm;
[0049] The distance between two adjacent grooves is 10 to 80 μm.
[0050] Optionally, the mass ratio of polyvinyl alcohol, water and sulfuric acid in step (2) is 1:10:0.5-5;
[0051] Among them, the mass of polyvinyl alcohol is calculated based on the mass of the substance itself, the mass of water is calculated based on the mass of the substance itself, and the mass of sulfuric acid is calculated based on the mass of the substance itself.
[0052] Preferably, the mass ratio of polyvinyl alcohol, water and sulfuric acid in step (2) is 1:10:0.5-1.5;
[0053] Among them, the mass of polyvinyl alcohol is calculated based on the mass of the substance itself, the mass of water is calculated based on the mass of the substance itself, and the mass of sulfuric acid is calculated based on the mass of the substance itself.
[0054] Optionally, in step (3), the mass ratio of the interdigitated electrode to the electrolyte is 1:0.5-1000.
[0055] Preferably, the mass ratio of the interdigitated electrode to the electrolyte in step (3) is 1:50-800.
[0056] Optionally, the mass ratio of the interdigitated electrode to the electrolyte is independently selected from any value of 1:0.5, 1:2, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:800, 1:1000 or any range between two of them.
[0057] Optionally, the coating further includes a drying step.
[0058] Optionally, the drying time is 0.1 to 72 hours.
[0059] Compared with the prior art, this application has the following beneficial effects:
[0060] (1) The present application provides a simple microstructure construction method, in which the electrode material is 3D printed into a cross-finger electrode pattern, and the electrode thickness is controlled by the number of printed layers, and then a grooved graphene-based thick electrode is prepared by laser etching. The electrode is etched contactlessly, no impurities are introduced, and no subsequent cleaning is required, thereby ensuring the stability of the structure and a simple preparation process.
[0061] (2) Compared with traditional thick-electrode microcapacitors, the supercapacitor provided in this application has optimized capacity and significantly improved mechanical properties, and is flexible while having high surface capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is an optical microscope photograph of a layer of interdigitated electrodes 3D printed in Example 1 of the present application;
[0063] Figure 2 The cross-sectional scanning electron microscope images of 3D printed 3-layer, 5-layer, and 7-layer electrodes in Comparative Example 1 of the present application (named 3l, 5l, and 7l from left to right, respectively), with a scale of 100 microns;
[0064] Figure 3 The cross-sectional scanning electron microscope images of the laser-etched 3-layer, 5-layer, and 7-layer electrodes in Example 1 of the present application (named 311, 511, and 711 from left to right, respectively), with a scale of 100 microns;
[0065] Figure 4 Optical microscope photos of comparative example 1 (left) and example 1 (right) of the present application under bending;
[0066] Figure 5 The microcapacitance of the conventional thick electrodes (3l, 5l, 7l) with different thicknesses in Comparative Example 1 is 5mV·s -1 Cyclic voltammogram at a scan rate of ;
[0067] Figure 6The microcapacitance of the grooved electrodes (311, 511, 711) with different thicknesses in Example 1 of the present application is 5mV·s -1 Cyclic voltammogram at a scan rate of ;
[0068] Figure 7 The performance attenuation comparison between the conventional thick electrode microcapacitor 71 in comparative example 1 and the groove electrode microcapacitor 711 in embodiment 1 of the present application after being bent 100 times at angles of 30°, 60°, 90°, 120°, 150°, and 180°;
[0069] Figure 8 The surface capacitance of the grooved electrode microcapacitor 711 in Example 1 of the present application changes with the current density. DETAILED DESCRIPTION
[0070] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0071] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0072] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0073] The analysis methods in the following examples are as follows:
[0074] The cyclic voltammetry and constant current charge-discharge analysis were carried out using a Chenhua 760E electrochemical workstation.
[0075] Example 1
[0076] Preparation of two-dimensional interdigitated electrodes:
[0077] Graphene, activated carbon, additives (hydroxyethyl cellulose: hydroxypropyl methyl cellulose = 1:1, mass ratio), and water were mixed in a mass ratio of 15:5:3:300, ground, and then 3D printed to obtain a layer of interdigitated electrodes.
[0078] The two-dimensional pattern of the interdigitated electrodes is shown in the top view. Figure 1 As shown, the finger spacing is 1 mm and the finger width is 330 μm.
[0079] Example 2
[0080] A method for preparing a high surface capacity flexible supercapacitor, the steps are as follows:
[0081] (1) Graphene, activated carbon, additives (hydroxyethyl cellulose: hydroxypropyl methyl cellulose = 1:1, mass ratio), and water are mixed in a mass ratio of 15:5:3:300, ground, and 3D printed into interdigitated electrodes of different thicknesses (3 layers, 5 layers, 7 layers), and then the thick interdigitated electrodes of different thicknesses (3 layers, 5 layers, 7 layers) are etched into interdigitated electrodes with a periodically arranged grooved microstructure in the longitudinal section by laser etching, wherein in the longitudinal section of the interdigitated electrode, the width of each groove is 160 μm (3 layers), 160 μm (5 layers), and 160 μm (7 layers), respectively, the depth of each groove is 140 μm (3 layers), 300 μm (5 layers), and 460 μm (7 layers), respectively, and the distance between two adjacent grooves is 40 μm (3 layers), 40 μm (5 layers), and 40 μm (7 layers), respectively, to obtain grooved interdigitated electrodes of different thicknesses;
[0082] (2) mixing polyvinyl alcohol, water and sulfuric acid in a mass ratio of 1:10:1 to obtain an electrolyte;
[0083] (3) The electrolyte obtained in step (2) is coated on the grooved interdigitated electrode obtained in step (1) (the mass ratio of the grooved interdigitated electrode to the electrolyte is 1:500) to obtain a high surface capacity flexible supercapacitor.
[0084] Comparative Example 1
[0085] A method for preparing a supercapacitor, comprising the following steps:
[0086] (1) Graphene, activated carbon, additives (hydroxyethyl cellulose: hydroxypropyl methyl cellulose = 1:1, mass ratio), and water were mixed in a mass ratio of 15:5:3:300, ground, and 3D printed into interdigitated electrodes of different thicknesses (3 layers, 5 layers, and 7 layers);
[0087] (2) mixing polyvinyl alcohol, water and sulfuric acid in a mass ratio of 1:10:1 to obtain an electrolyte;
[0088] (3) coating the electrolyte obtained in step (2) on the interdigital electrodes obtained in step (1) (the mass ratio of the interdigital electrodes to the electrolyte is 1:500) to obtain a supercapacitor.
[0089] Experimental Example 1
[0090] The supercapacitors prepared in Example 1 and Comparative Example 1 were subjected to electrochemical tests, and the test methods included cyclic voltammetry test, constant current charge-discharge test and flexibility test.
[0091] The thickness of the interdigitated electrodes in Comparative Example 1 is as follows Figure 2As shown, 3l, 5l, and 7l are 260 microns, 420 microns, and 580 microns respectively.
[0092] The thickness of the grooved interdigitated electrodes in Example 1 is as follows: Figure 3 As shown, 3ll, 5ll, and 7ll are 260 microns, 420 microns, and 580 microns respectively.
[0093] The flexibility of the grooved interdigitated electrode (711) in Example 1 and the conventional thick electrode (71) in Comparative Example 1 under bending is as follows: Figure 4 As shown by Figure 4 It can be clearly seen that cracks already exist in the conventional thick electrode in Comparative Example 1, while the morphology of the grooved interdigitated electrodes in Example 1 of the present application remains almost unchanged.
[0094] Typical test results are as follows: Figure 5 and Figure 6 As shown by Figure 5 and Figure 6 It can be seen that the performance of the groove electrode microcapacitor in Example 1 of the present application is better than that of the traditional thick electrode microcapacitor in Comparative Example 1.
[0095] Typical test results are as follows: Figure 7 As shown by Figure 7 It can be seen that the mechanical properties of the groove electrode microcapacitor in Example 1 of the present application are much higher than those of the traditional thick electrode microcapacitor in Comparative Example 1.
[0096] Typical test results are as follows: Figure 8 As shown by Figure 8 It can be seen that the microcapacitance of the grooved electrode in Example 1 (711) of the present application is 0.5 mA·cm -2 Can reach 200mF·cm -2 .
[0097] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A high surface capacity flexible supercapacitor, characterized in that: The high surface capacity flexible supercapacitor comprises interdigital electrodes and an electrolyte; The longitudinal section of the interdigitated electrodes is in the shape of periodically arranged grooves; The electrolyte covers the interdigitated electrodes; The interdigital electrodes are flexible.
2. A high surface capacity flexible supercapacitor according to claim 1, characterized in that: In the longitudinal section of the interdigitated electrode, the width of each groove is 50 to 200 μm; The depth of each groove is 10 to 1000 μm; The distance between two adjacent grooves is 10 to 80 μm; Preferably, the thickness of the interdigital electrode is 20 to 2000 μm; Preferably, the mass ratio of the interdigital electrodes to the electrolyte is 1:0.5-1000.
3. The high surface capacity flexible supercapacitor according to claim 1, characterized in that: The raw materials for preparing the interdigital electrodes include graphene, activated carbon and additives; Preferably, the mass ratio of the graphene, activated carbon and additive is 2-45:1-10:1; Among them, the mass of graphene is measured by the mass of the substance itself, the mass of activated carbon is measured by the mass of the substance itself, and the mass of additives is measured by the mass of the substance itself.
4. A high surface capacity flexible supercapacitor according to claim 3, characterized in that: The additives include hydroxyethyl cellulose and hydroxypropyl methyl cellulose; Preferably, the mass ratio of the hydroxyethyl cellulose to the hydroxypropyl methyl cellulose is 1:0.5-1.
5.
5. The high surface capacity flexible supercapacitor according to claim 3, characterized in that: The raw materials for preparing the interdigital electrodes also include water.
6. The high surface capacity flexible supercapacitor according to claim 1, characterized in that: The electrolyte includes polyvinyl alcohol and sulfuric acid; Preferably, the mass ratio of polyvinyl alcohol to sulfuric acid is 1:0.5-5; Among them, the mass of polyvinyl alcohol is calculated based on the mass of the substance itself, and the mass of sulfuric acid is calculated based on the mass of the substance itself; Preferably, the electrolyte also includes water.
7. The method for preparing a high surface capacity flexible supercapacitor according to any one of claims 1 to 6, characterized in that: The steps include: (1) Printing and etching a mixture containing graphene, activated carbon, additives and water in sequence to obtain interdigitated electrodes; (2) mixing polyvinyl alcohol with water and sulfuric acid to obtain an electrolyte; (3) The electrolyte obtained in step (2) is coated on the interdigital electrode obtained in step (1) to obtain a high surface capacity flexible supercapacitor.
8. The method for preparing a high surface capacity flexible supercapacitor according to claim 7, characterized in that: The mass ratio of graphene, activated carbon, additive and water in step (1) is 2-45:1-10:1:0.001-1000; Among them, the mass of graphene is calculated based on the mass of the substance itself, the mass of activated carbon is calculated based on the mass of the substance itself, the mass of additives is calculated based on the mass of the substance itself, and the mass of water is calculated based on the mass of the substance itself; Preferably, the additives in step (1) include hydroxyethyl cellulose and hydroxypropyl methyl cellulose; The mass ratio of the hydroxyethyl cellulose to the hydroxypropyl methyl cellulose is 1:0.5-1.5; Preferably, the thickness of the interdigitated electrode in step (1) is 20 to 2000 μm; Preferably, the longitudinal section of the interdigitated electrodes in step (1) is in the shape of periodically arranged grooves; Preferably, the interdigitated electrodes in step (1) are flexible; Preferably, in the longitudinal section of the interdigitated electrode in step (1), the width of each groove is 50 to 200 μm; The depth of each groove is 10 to 1000 μm; The distance between two adjacent grooves is 10 to 80 μm.
9. The method for preparing a high surface capacity flexible supercapacitor according to claim 7, characterized in that: The mass ratio of polyvinyl alcohol, water and sulfuric acid in step (2) is 1:10:0.5-5; Among them, the mass of polyvinyl alcohol is calculated based on the mass of the substance itself, the mass of water is calculated based on the mass of the substance itself, and the mass of sulfuric acid is calculated based on the mass of the substance itself.
10. The method for preparing a high surface capacity flexible supercapacitor according to claim 7, characterized in that: The mass ratio of the interdigital electrode to the electrolyte in step (3) is 1:0.5-1000; Preferably, after the coating is completed, a drying step is also included; Preferably, the drying time is 0.1 to 72 hours.